Consumer additive manufacturing or 3D printing adoption: an exploratory study. Issue 7 (5th September 2016) - Steenhuis, Harm-Jan; Pretorius, Leon
Abstract : Purpose: The purpose of this paper is to explore what underlies the development of the consumer 3D printing industry and gain insight into future developments and its potentially disruptive impact on the existing manufacturing industry. Design/methodology/approach: A combination of approaches was followed. Initially a consumer 3D printer was purchased to gain first-hand experience as part of a practical research case study. Results were discussed with manufacturers and additional information was sought, and triangulated, via a survey and an exploratory bibliometric study. Findings: Many characteristics are in place to identify consumer 3D printing as a potential disruptive technology for the manufacturing industry. For example, the cost of consumer 3D printing is lower than for traditional manufacturing. However, the current adoption rate is low and the user friendliness and technological capabilities need to improve. Research limitations/implications: The main limitation is the exploratory nature of the study which does not allow generalizations. Practical implications: If developments and adoption patterns continue, then traditional manufacturing industries, distribution channels and the transportation sector may become threatened. Social implications: Technological advances in consumer manufacturing can potentially threaten several economic sectors, which can lead to loss of jobs and affect budgets of states of countries that depend on sales tax. Originality/value: One of the first studies to employ experiments in combination with other methods to gain insight into adoption patterns and the disruptive nature of consumer 3D printers specifically, rather than industrial 3D printers or new business models as a result of 3D printing technology.